ANALISIS EFEKTIVITAS MODEL GROW ME DALAM SUPERVISI AKADEMIK DI SEKOLAH DASAR - Wattimena, Janty; Dwikurnianingsih, Yari; Sanoto, Herry (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This study aims to analyze the effectiveness of the GROW ME model in academic supervision at SD Negeri Inpres Sereh, Jayapura Regency. The GROW ME model, which consists of the steps of Goal, Reality, Options, Will, Monitoring, and Evaluation, is designed to help teachers formulate learning objectives, evaluate the current situation, explore various solution options, and plan concrete action steps. This study aims to analyze the effectiveness of the application of the GROW ME model in the context of academic supervision. Through quantitative and qualitative methodologies, data were collected from observations, interviews, questionnaires and document analysis related to the implementation of academic supervision, involving teachers and principals. The results of the study indicate that the application of the GROW ME model in academic supervision can increase teacher involvement in the learning process and facilitate their professional development. This study concludes that the GROW ME model is an effective approach to improving the quality of academic supervision in elementary schools, and recommends its wider application in educational contexts. These findings are expected to provide a positive contribution to the development of more efficient and beneficial supervision practices in educational environments.